Speculation about some political impacts of the catholic school prison form: A Colombian case - Congote Ochoa, Bernardo (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The article intends to prove that a certain form of imprisonment in force in the Catholic confessional school would influence the social way of doing politics. First, it describes briefly the evolution of the school model with milestones in the Colombian colonial and republican periods. And from Foucault's hand, he discusses both the normalizing sanction applied to the student and the panoptic design of the school building, both framed in the Lasallian and Jesuit models. Secondly, it generates as a result, first, how the school prison form is configured in Colombia, analyzing a specific comparative case between a school and a prison; and, second, it defines some of the political impacts that this school model would have brought on Colombia. The fundamental finding consists in demonstrating how in the form of a school prison, on a case-by-case basis, the rules that govern a prisoner closely resemble those that govern the behavior of a schoolboy. The article concludes by proving that school concepts - prisons of moral order, liberality and education would contribute to planting in students a certain proclivity to favor, in their exercise of politics, authoritarian-violent models of government.